1996
DOI: 10.1097/00005373-199605000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Straight Pin Aspiration in Young Women

Abstract: Straight pins are used extensively for securing facial scarves in women and girls in the Middle East. Accidental aspiration often results in the pin lodging in the segmental bronchus with the sharp end pointing cephalad. Flexible bronchoscopy is superior to rigid bronchoscopy in retrieving these pins. We report on five cases successfully treated by fiberoptic bronchoscopy under general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 3 publications
1
20
0
3
Order By: Relevance
“…10 In several studies from the Middle East, turban pins were the most common type of foreign body aspirated, as they are held between the teeth while tying the traditional turban. 27,28,39,40 The most common location for a foreign body in the airway is the right bronchial tree, particularly the right lower-lobe and intermediate bronchi, due to the vertical orientation of the right main bronchus. 1,2,4,14 Bilateral foreign bodies were present in only one subject and are rare.…”
Section: Discussionmentioning
confidence: 99%
“…10 In several studies from the Middle East, turban pins were the most common type of foreign body aspirated, as they are held between the teeth while tying the traditional turban. 27,28,39,40 The most common location for a foreign body in the airway is the right bronchial tree, particularly the right lower-lobe and intermediate bronchi, due to the vertical orientation of the right main bronchus. 1,2,4,14 Bilateral foreign bodies were present in only one subject and are rare.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, the removal of the foreign body leads to resolution of the parenchymal or bronchial pathology and prevents unnecessary surgery [10, 11]. Considering the diagnostic approaches for TFBA and therapeutic approaches for distally localized TFBA, flexible bronchoscopy (FB) is superior to rigid bronchoscopy (RB) [9, 12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the location and type of the foreign body, the experience of the bronchoscopist and the availability of appropriate instruments. Although there are many reports of removing other foreign bodies by using FB [1,17,18,19], there are few reports of removing pins by FB [3, 4, 12]. Moreover, the few reported studies contain insufficient information on the key aspects of foreign body removal by using FB.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other authors preferred FOB. In a series of 5 cases described by Shabb et al [15], FOB under general anesthesia was used in all cases. Recently, Gokirmak et al [16] retrospectively reported the usefulness of FOB under local anesthesia in the retrieval of 8/11 aspirated turban pins (73%).…”
Section: Discussionmentioning
confidence: 99%
“…The rigid bronchoscope (RB) is used to be the traditional method of removal [13] [14]. However, recently the fiberoptic bronchoscope (FOB) is increasingly reported to be used for this purpose [15] [16] [19] [20] [21]. The aim of this study is to explore the effectiveness and safety of FOB for extraction of aspirated headscarf pins.…”
Section: Introductionmentioning
confidence: 99%